Komposisi Ikan Hasil Tangkapan Pukat Cincin pada Berbagai Koordinat di Perairan Laut Jawa - Muhammad Maskur; Nurwahidin Nurwahidin; Arham Rumpa; Tri Setianto; Khaerudin Isman; Tamrin Tamrin; Paduartama Tandipuang (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
This study aims to identify the composition of fish capture and the number of catches with purse seine at various coordinates in the fisheries management area (WPP) 712, namely the Java sea. The study was carried out on several coordinates in the Java sea waters when the ship was operating the purse seine fishing gear. The data generated were 25 coordinates in the operation of fishing gear with the composition of the catch of 10 species of fish, namely mackerel, banyar fish, black pomfret, tetengkek fish, tongkol fish, ceramic fish, tembang fish, japuh fish, selar fish, and squid. The data analyzed using Anova Two Factor Without Replication, where this analysis is used to test the average difference based on rows (fish species) and columns (coordinates). The results showed that Coordinate 8 is a fishing area that produces the highest number of catches of 6000 kg with the type of fish caught namely 1000 kg of selar fish, 4500 kg of tetengkek fish, 400 kg of black pomfret and mackerel of 100 kg and at coordinate 14 is a fishing area that produces the lowest number of catches of 400 kg, with the types of fish caught are 50 kg black pomfret, 200 kg of tetengkek fish, 100 kg of japuh fish, 20 kg of anchor fish and 30 kg of squid . Anova Two Factor Without Replication analysis results show that there are differences in the average number of catches based on fish species in the fishing ground area